Zinc-Nickel Codeposition in Sulfate Solution Combined Effect of Cadmium and Boric Acid - Y. Addi; A. Khouider (International Journal of Electrochemistry)
The combined effect of cadmium and boric acid on the electrodeposition of zinc-nickel from a sulfate has been investigated. The presence of cadmium ion decreases zinc in the deposit. In solution, cadmium inhibits the zinc ion deposition and suppresses it when deposition potential value is more negative than −1.2 V. Low concentration of CdSO4 reduces the anomalous nature of Zn-Ni deposit. Boric acid decreases current density and shifts potential discharge of nickel and hydrogen to more negative potential. The combination of boric acid and cadmium increases the percentage of nickel in the deposit. Boric acid and cadmium.